Prekmurje (Trans-Mura region) and Prekmurian language - Josipovič, Damir (Anali PAZU, 2022)
The article presents an outline of Prekmurian language spatial and historical development and use, and its statistical quantification. Prekmurian language was an official statistical category at the last Yugoslav census of 1991. Little is known nowadays that as much as one third of the population of Prekmurje declared both Prekmurian as its domestic colloquial language and its local colloquial language in 1991. In contrast to colloquial language, Prekmurian as a mother tongue was quite rarely stated, while opting for Prekmurian ethnicity was precluded. Owing to the results of the 1991 census, the article aims at analyzing the causes of statistical appearance of Prekmurian in censuses, its historical-geographical scope and use, and the semi-recent local disparities in degrees of stating Prekmurian as a mother tongue or domestic and local colloquial language respectively. The initial hypothesis of the research claimed that the protestant adherence was crucial in people’s reporting the Prekmurian as its domestic (within families) or local colloquial language. To evaluate that hypothesis we employed the spatial and statistical analyses of census data on Prekmurian speakers and found some unexpected results.Key words: Prekmurian language, Prekmurians, Prekmurje, Trans-Mura region, religion,
Keywords: Prekmurian language; Prekmurians; Prekmurje; Trans-Mura region; religion